Diversidade fenotípica e genotípica de bactérias endofíticas isoladas de raízes de Castanheira-do-Brasil (Bertholletia excelsa H.B.K) em três municípios de RR - Chalita, Patrícia Bombonati (2016)
This study aimed to characterize phenotypic and genotypically bacteria isolated from roots of the Brazil nut tree cultivated and native and evaluate the presence of features able to promote the plant growth. A total of 303 bacteria were isolated from roots of Brazilian nut tree, of these 81 are from a monoculture of nuts, 154 from a SAF and 68 from a native rainforest. The bacteria were isolated by using semisolid media NFB, LGI, JMV and DYG’S. The phenotypic characterization of bacteria was assessed by analysis of total protein by SDS-PAGE, solubilization of calcium phosphate in solid medium, solubilization of aluminium fosfate in liquid medium and production of indoleacetic acid. Based on protein profiles (SDS-PAGE) was estimated the Shannon diversity index and rarefaction analysis. The genotypic characterization was performed through presence or absence of the nifH gene and by partial sequencing of 16S rRNA gene. The protein profiles were obtained of 290 bacteria. Through the analysis of protein profiles were generated four dendrograms for each medium of isolation, JMV, LGI, DYG'S and NFB. From these dendrograms, it was realized the selection of bacteria groups formed at 80% similarity in each medium of isolation, being selected 100 bacteria. The Shannon diversity index was similar for the three areas where the bacteria were isolated. Of the 100 bacteria evaluated for calcium phosphate solubilizing capacity, it was observed that 69% presented this feature and 90% of bacteria were able to solubilize aluminum phosphate in liquid medium. A total of 70 bacteria synthesized indole acetic acid, 44 in medium with the absence of tryptophan, 61 with tryptophan and 35 presented in medium with or without tryptophan. Only 18 bacteria presented positive amplification for the nifH gene, of these eight were isolated in semi selective media for Azospirillum sp. (NFB and LGI), and 10 isolated from non-selective medium (DYG'S). Among the evaluated bacteria, 24 have potencial for future tests of inoculation in the seedlings production. These bacteria presented at least two or more characteristics of plant growth promotion. Through the partial sequencing of 16S rRNA gene, the obtained nucleotide sequences resulted in distribution of the bacteria in 18 different genera. It was detected sequences of genera belong to α-Proteobacteria, β-Proteobacteria, γ-Proteobacteria, Bacilli and Actinobacteria class. These results indicate a high diversity of genera of endophytic growth-promoting bacteria present in the roots of Brazilian nut tree. This is the first work of characterization of endophytic growth-promoting bacteria in roots of Brazilian nut tree.